Lived experiences of clinical instructors in facilitating online related learning experiences among nursing students in the Philippines: Challenges, adaptations, and insights - Rimando, Yves Mariel; Chua, Loresita Antonia A.; Trajera, Sheilla M.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
This study explores the lived experiences of Clinical Instructors (CIs) in facilitating online Related Learning Experiences (RLE) for nursing students during the 2020–2021 academic year in three higher education institutions (HEIs) in Bacolod City, Philippines. Using a qualitative phenomenological approach, in-depth semi-structured interviews were conducted with nine nursing faculty members to understand their motivations, challenges, and adaptations in transitioning from face-to-face to online RLE delivery. Purposive sampling was used to select participants who had prior clinical teaching experience before the COVID-19 pandemic. Findings revealed three major themes: 1) Adapting to Changes in Teaching and Learning, which emphasized the development of new skills, knowledge updates, and emotional adjustments; 2) Challenges in Online RLE, highlighting technical inadequacies, resource limitations, and external constraints such as poor internet connectivity and power interruptions; and 3) Growth and Professional Development, underscoring the instructors’ resilience and professional advancement despite these difficulties. The study concludes that enhancing digital infrastructure and revising the nursing curriculum to incorporate technology-driven pedagogies are essential for improving online RLE delivery. These findings provide practical insights for HEIs and policymakers in strengthening faculty training, digital literacy, and resource accessibility, ensuring the effectiveness of online nursing education in future crises.